WALHI's Role in International Advocacy on Alleged Human Rights Violations: by PT Astra Agro Lestari in Central Sulawesi - Ilham, Muhammad; Thariq Afdhala; Al Bukhori Gymastiar (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2025)
This study focuses on analyzing the role of Wahana Lingkungan Hidup Indonesia (WALHI) in advocating for the Astra Agro Lestari (AAL) palm oil case in international forums. The AAL palm oil case in Central Sulawesi and West Sulawesi has been in the spotlight due to land grabbing, environmental pollution, and human rights violations against indigenous peoples and local farmers. This study also comprehensively discusses WALHI's strategies in conducting advocacy in international forums. The Transnational Advocacy Networks theoretical framework is used to help analyze the case in this study, with a focus on WALHI's role and strategies in advocating the AAL palm oil case in international forums. Through literature analysis of secondary data and structured interviews as primary data, this study found that WALHI's actions constitute transnational advocacy network practices. In this case, WALHI significantly utilizes its membership in Friends of the Earth International (FoEI) as a means of advocating at international forums, thereby gaining the attention of the United Nations through the publication of Special Rapporteurs. This study concludes that in the AAL palm oil case, WALHI has significantly contributed to advocating for the AAL palm oil case in international forums through its strategy of leveraging its relationships within FoEI. This study contributes to education on the role and strategies employed by NGOs like WALHI in international advocacy practices using the Transnational Advocacy Networks (TANs) theory.